The bold ones : innovate and disrupt to become truly indispensable - Kanungo, Shawn (McGraw Hill, 2023)
"A practical and inspirational playbook that shows you how to use innovation and disruption to become truly unstoppable. Disruption for disruption's sake isn't a smart strategy when you're seeking ways to accelerate your career and become truly indispensable. In The Bold Ones, you'll discover it's more about being "dangerous" than disruptive: being simultaneously bold enough to challenge industries, yet practical enough to recreate them"--